Relative Hyperlactatemia in the Emergency Department - Bou Chebl, Ralphe; Jamali, Sarah; Mikati, Nancy; Al Assaad, Reem; Abdel Daem, Karim; Kattouf, Nadim; Safa, Rawan; Makki, Maha; Tamim, Hani; Abou Dagher, Gilbert (Frontiers in Medicine, 2020)
Objective: The clinical interpretation of lactate ≤ 2.00 mmol/L in emergency department (ED) patients is not well characterized. This study aims to determine the optimal cutoff value for lactate within the reference range that predicts in-hospital mortality among ED patients. Methods: This was a retrospective study of adult patients presenting to a tertiary ED with an initial serum lactate level less than 2.00 mmol/L. The primary outcome was in-hospital mortality. Youden’s index was utilized to determine the optimal threshold that predicts mortality. Patients above the threshold were labeled as having relative hyperlactatemia. Results: During the study period, 1638 patients were included. The mean age was 66.9 ± 18.6 years, 47.1% of the population were female, and the most prevalent comorbidity was hypertension (56.7%). The mean lactate level at presentation was 1.5 ± 0.3 mmol/L. In-hospital mortality was 3.8% in the overall population and 16.2% were admitted to the ICU. A lactate of 1.33 mmol/L was found to be the optimal cutoff that best discriminates between survivors and non-survivors. Relative hyperlactatemia was an independent predictor of in-hospital mortality (OR 1.78 CI1.18-4.03; p 0.02). Finally, Relative hyperlactatemia was associated with increased mortality in patients without hypertension (4.7% versus 1.1%; p 0.008), as well as patients without diabetes or COPD. Conclusion: The optimal cutoff of initial serum lactate that discriminates between survivors and non-survivors is in the ED 1.33 mmol/L. Relative hyperlactatemia is associated with increased mortality in emergency department patients, and this interaction seems to be more important in healthy patients.